Empirical assessment of seismic design hazard’s exceedance area - Iunio Iervolino (Nature Portfolio, 2021)
Abstract Design ground motion intensities determine the actions for which structures are checked, in the conventional approach of seismic codes, not to fail the target performances. On the other hand, due to inherent characteristics of probabilistic seismic hazard analysis (PSHA), it is expected that site-specific design intensity based on PSHA is exceeded in the epicentral area of moderate-to-high magnitude earthquakes. In the context of regional seismic loss assessment and of the evolution of seismic codes from the regulator perspective, it is useful to gather insights about the extent of the zone around the earthquake source where code-conforming structures are expected to be systematically exposed to seismic actions larger than those accounted for in design. To assess such areal extent based on empirical evidence is the scope of the study presented in the paper. To this aim, peak ground acceleration ShakeMap data for Italian earthquakes from 2008 to 2020 were compared to the current design intensities in the same areas for which the maps are available. This allowed, first, to develop simple semi-empirical models of the exceedance area versus the magnitude of the earthquakes. Second, it allowed to model the probability that an earthquake of given magnitude causes exceedance of the design intensity via logistic regressions. Coupling the first and second class of models provides an approximation of the expected exceedance (logarithmic) area upon occurrence of an earthquake of given magnitude. Such an area can be of several thousand square kilometers for earthquakes occurring relatively frequently in countries such as Italy.